Experiences of patients waiting for rapid HIV test results in Phela-o-Phedishe clinic at Mankweng hospital, Limpopo Province, South Africa - Mothiba, T. M.; Malema, R. N. (My University, 2014)
This study was aimed at determining the experiences of patients waiting for rapid HIV test results in Phela-o-Phedishe clinic at Mankweng hospital, Limpopo Province, South Africa. A descriptive, exploratory and contextual qualitative research design was used. Non-probability purposive sampling was used to select participants for this study. A total of 15 patients who took a rapid HIV test were included in the unstructured interview sessions. Tesch’s (1990) open coding data analysis method. The findings revealed that participants had experienced negative feelings waiting for a rapid HIV test results and gave reasons for the feelings experienced during waiting period as well as reasons for taking the test. There is a need for patients taking a rapid HIV test to be given a chance to think through the decision of being tested. Awareness campaigns on the importance of a rapid HIV test should be initiated in which support groups in communities are encouraged to share ideas and views about HIV testing. The support groups should also include old and young people so that they support one another.
Published in: African Journal for Physical, Health Education, Recreation and Dance (AJPHERD) Supplement 1:1 (June), 2014, pp. 68-79.
Keywords: HIV test experiences; AIDS (Disease) -- South Africa